Evaluation of microkinesitherapy effectiveness in post-traumatic cervicalgia: a new approach applied to previous data - Baconnier, Pierre; Vial, Bruno; Vaudaux, Gérard; Vaudaux, Geneviève; Bosson, Jean-Luc (Manual Therapy, Posturology & Rehabilitation Journal, 2019)
Background. Cervicalgia from traumatic events such as road traffic accidents and falls can lead to musculoskeletal and soft tissue injuries with the development of pain and headache. Microkinesitherapy is a manual therapy technique that normalizes soft tissue tensions and articular range of motion throughout micropalpation. Objective. This study is a secondary analysis with a clinical significance approach to data collected in a previously published study. These data were obtained during a randomized double-blind clinical trial to evaluate the effectiveness of microkinesitherapy treatment in cervical trauma. Methods. The authors performed a secondary analysis of a previous randomized, double-blind clinical trial, using the Minimal Clinically Important Difference (MCID). This study was conducted at the Faculty of medicine of the Université Grenoble Alpes (Grenoble, FRA), and analyzed 29 patients with cervical trauma less than three months of trauma. This is a secondary analysis of data collected in a previously published randomized double-blind clinical trial where the treated group received a microkinesitherapy treatment (n= 15, 8 females) and the other group received a sham treatment (n=14, 7 females). To look at the clinical significance of those results, it was used the MCID of the instantaneous pain and cervical articular mobility, before and after the treatment or sham treatment. The clinical significance of the treatment was obtained through an inter-group comparison (Pearson’s chi-squared test) based on MCID. Results. With both threshold values, the Pearson’s chi-squared test provide a significant difference in the treatment result compared to sham group. Conclusion. The use of the MCID concept and its value is drawn from recent studies on neck pain allowed us to demonstrate, on an intergroup analysis basis, that there is a clinically significant difference in the effect of a microkinesitherapy treatment on post-traumatic neck pain as compared to a sham treatment.